Erratum: Hypersensitive H2 sensor based on polymer planar Bragg gratings coated with Pt-loaded WO3–SiO2 (Optics Letters (2020) 45 (3601) DOI: 10.1364/OL.395341) - Kefer, Stefan; Dai, Jixiang; Yang, Minghong; Schmauß, Bernhard; Hellmann, Ralf (Optics Letters, 2020)
We present an erratum to our Letter [Opt. Lett. 45, 3601 (2020)]. Labeling errors in two figures and an incorrect sentence are revised. The corrections have no influence on the conclusions of the original Letter. In Figs. 2(b) and 4 of [1], the respective labeling of TE andTM reflection peak is corrected, as it is interchanged in the original publication. According to Fig. 4, the TM peak’s wavelength shift is approximately 5% greater than that of the TE reflection signal. This circumstance is also interchanged in the original Letter [1].
CRIS-Team Scopus Importer:2021-04-19